Research on Hydrodynamic Performance of a 30 kW Rim-Driven Thruster and Its Coupling Mechanism with an AUV - Xia Yang; Kunkun Li; Xiong Deng; Dingfeng Yu; Yiyun Peng; Yan Luo; Yanyang Wu (Journal of Marine Science and Engineering, 2026)
With the continuous expansion of deep-sea resource exploration, marine environmental monitoring, and underwater operations, Autonomous Underwater Vehicles (AUVs) have been increasingly widely applied. Aiming at the demand for high-performance main propulsion systems of Autonomous Underwater Vehicles (AUVs), this paper conducts research on the structural design and hydrodynamic performance of a 30 kW rim-driven thruster (RDT) and its coupling mechanism with AUVs. By combining computational fluid dynamics (CFD) simulations and experimental methods, the influence of the advance coefficient on the open-water performance of the thruster is revealed. An integrated coupling simulation model of the AUV and RDT is established to analyze the performance attenuation law of the thruster and the characteristics of the coupled flow field under wake flow conditions, and to clarify the two-way interaction mechanism between the thruster and AUV. Towing tank tests were carried out at sailing speeds ranging from 1 to 4 kn, which verifies the reliability of the numerical simulation model and the matching performance between the thruster and AUV. The results show that the open-water efficiency of the thruster reaches a peak value of 0.536 at the advance coefficient J=0.8, which is close to the optimal efficiency range with good matching performance of the propulsion system Under wake flow conditions, the attenuation range of the thrust coefficient of the thruster is 12.45–16.53% with the increase in advance coefficient. The main reasons are the uneven inflow velocity and unstable flow field pressure distribution caused by the non-uniform wake flow at the AUV stern. At the ship speeds of 2 kn, 3 kn and 4 kn, the self-propulsion rotational speeds obtained from test fitting are in good agreement with the simulation results, with all relative errors less than 8%. This study provides a theoretical basis and technical reference for the engineering design of medium and high-power rim-driven thrusters as well as the matching optimization of AUV-thruster systems.

Structural Design and Performance Analysis of Underwater Tethered Vehicles - Yan Luo; Xinming Xiong; Xia Yang; Xiong Deng; Dingfeng Yu; Yiyun Peng; Yanyang Wu (Journal of Marine Science and Engineering, 2026)
An underwater towed vehicle serves as an effective and widely applicable mobile marine observation platform. Existing towed vehicles rely heavily on cables for depth adjustment. They also suffer from poor hydrodynamic efficiency and insufficient instrument space. To address these limitations, this study developed a novel compensation control system. This system regulates the vehicle’s vertical movement and cable deployment by controlling the attack angles of its front and rear hydrofoils. The Myring profile was selected as the base design for the towed vehicle, offering excellent hydrodynamic performance, ample internal space, and cost-effectiveness. To verify the system’s reliability, critical components were meticulously designed and calibrated. Hydrodynamic simulations confirmed that adjusting the hydrofoil angle effectively controls vertical motion, with stress and deformation in the lifting mechanism and cable connectors meeting design specifications. Additionally, the overall drag resistance remains low, while the lift generated by both hydrofoils satisfies depth adjustment requirements. This research provides robust numerical foundations for developing vertical control strategies, optimizing operational conditions, and conducting subsequent sea trials of towed vehicles. Quantitative comparison with the conventional scheme indicates that the proposed structure cuts total drag by 21.6%, boosts depth adjustment efficiency by 47.3%, and achieves a 32% higher hydrofoil lift-drag ratio, accompanied by a structural safety factor of 1.8 and maximum deformation of only 1.711 mm under rated working conditions.

Investigation of mechanical properties of calcareous sand treated with a water-reactive polyurethane using acoustic emission - Jiajia Zheng; Dingfeng Cao; Chengchao Guo; Fuming Wang; Zhixia Liu; Jinghong Wu; Chao Teng; Deyong Wang (Marine Georesources & Geotechnology, 2026)

Energy-based method for the failure criterion and resistance evaluation of marine clay under cyclic loading - Xing Xiao; Xin Guan; Qi Wu; Dingfeng Zhao; Ruirong Zhou; Guoxing Chen (Engineering Geology, 2025)

Frozen and unfrozen moisture content estimation in coral calcareous sand during artificial freezing - Dingfeng Cao; Hong-hu Zhu; Wu Zhu; Zhixia Liu; He Wang; Jinghong Wu (Engineering Geology, 2024)

A green large-scale fabrication of cellulose-based multifunctional fluorescent fibers for versatile applications - Changjing Qiu; Fang Peng; Pingping Wu; Xijun Wang; Songnan Hu; Chuanlin Huang; Xingxing Li; Dingfeng Xu; Hui Li; Peng-Cheng Ma; Pan Chen; Haisong Qi (Chemical Engineering Journal, 2024)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Archaea, the tree of life, and cellular evolution in eukaryotes - Jing Xiao; Lu Fan; Dingfeng Wu; Yanbing Xu; Dengxun Lai; William F. Martin; Ruixin Zhu; Chuanlun Zhang (Science China Earth Sciences, 2019)

The MicroRNA-224 Inhibitor Prevents Neuronal Apoptosis via Targeting Spastic Paraplegia 7 After Cerebral Ischemia - Feng Fu; Dingfeng Wu; Chao Qian (Journal of Molecular Neuroscience, 2016)